2008
DOI: 10.1016/j.chembiol.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

A Heterospecific Leucine Zipper Tetramer

Abstract: Protein-protein interactions play an essential role in the assembly of the macromolecular complexes that form functional networks and control cellular behavior. Elucidating principles of molecular recognition governing potentially complex interfaces is a challenging goal for structural and systems biology. Extensive studies of alpha-helical coiled coils have provided fundamental insight into the determinants of one seemingly tractable class of oligomeric protein interfaces. We report here that two different va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 75 publications
(88 reference statements)
0
15
1
Order By: Relevance
“…Deng et al examined the structure and stability of GCN4‐pVe, GCN4‐pVg, GCN4‐pAe, and GCN4‐pAg in which either position e or g contained Val or Ala. These polypeptides formed tetramers, and it was shown that the hydrophobic side chain (Val or Ala) at position e or g contributed to one part of the hydrophobic surface with positions a and d .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Deng et al examined the structure and stability of GCN4‐pVe, GCN4‐pVg, GCN4‐pAe, and GCN4‐pAg in which either position e or g contained Val or Ala. These polypeptides formed tetramers, and it was shown that the hydrophobic side chain (Val or Ala) at position e or g contributed to one part of the hydrophobic surface with positions a and d .…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that GCN4‐pAA, a polypeptide that has Ala residues at positions e and g , produces a seven‐stranded coiled‐coil with a cavity within a hydrophobic core . In addition, substitution with Ala or valine (Val) at position g caused increased thermostability compared with the wild‐type amphipathic polypeptide, resulting in the formation of antiparallel tetramers . As mentioned above, it was also reported that the α‐helix assembly state changes depending on whether positions e and g are occupied by charged or hydrophobic amino acids .…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Higher ordered interactions could be achieved if trimeric or even tetrameric PIMs were developed. For example, Deng et al reported that two mutant GCN4 leucine zippers form anti-parallel heterospecific tetramers (62). These and similar PIMs might help researchers realize PIMAX applications involving more than two proteins, including enzymes with an obligatory co-factor, and trimeric or tetrameric protein complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Well-known exceptions are, in the case of proteins, hydrophobic interactions of nonpolar amino acid side chains, which can lead to highly ordered structural motifs, such as the leucine zipper, [1,2] and in the case of DNA, the double-helical Watson-Crick structure, in which the two nucleic acid strands are held together by intra-and interstrand aromatic stacking interactions between the nucleobases as the primary source of stability and by hydrogen bonding between the bases as the source of selectivity. Whereas the structural and energetic impact of hydrogen bonding is generally well appreciated, the understanding and prediction of the structural and energetic impact of stacking or hydrophobic interactions on biomolecular folding in water is comparably poor.…”
mentioning
confidence: 99%